Social - Psychological Aspects Of The Family - Baratullaeva Dilnoza Habibullo Qizi (Academia One Publishing, 2024)
The article talks about a number of psychological aspects of the functioning of the family as a social structure, in the family a person grows up, his mind, thoughts, worldview are formed, and a person perceives himself as a happy and peaceful place only in the family. In our country, it will be possible to solve the social problems of families, ensure their wellbeing, protect them psychologically with material and moral support.
Keywords: consciousness; thought; outlook; psychological protection